PENGEMBANGAN BAHAN AJAR BERBASIS BUKU SAKU PADA MATERI TATA CARA SHALAT SISWA KELAS II SD - Leni, Leni Nova Sari; Romadon; Adi Saputra (Universitas Muhammadiyah Bangka Belitung, 2023)
This research was motivated due to a lack of references for learning on the materials of prayer procedures. In addition, the size of the textbook is also less practical to carry everywhere due to its size, and teaching materials based on pocketbooks have not yet been compiled on the materials of prayer procedures in Islamic education. This study aims to develop a pocketbook on the materials of prayer products for second-grade students at elementary school. This research was a research and development (Research and Development). This study used the ADDIE model which consists of five stages: analysis, design, development, implementation, and evaluation. This study shows that teaching materials based on pocketbooks are feasible and practical as learning media by revising them based on expert advice. The percentage of eligibility given by subject matter expert 1 is 90% (very feasible), by material expert 2 is 84% (very feasible), by media expert is 80% (decent), and by education practitioner expert is 84% (practical). The percentage of eligibility given from the results of the teaching materials trial (small scale) obtained a percentage of 100% (very feasible) and the results of the trial use of teaching materials (large scale) obtained a percentage of 96% (very feasible). So it can be concluded that the pocket book-based teaching materials that have been developed are feasible and practical to use as learning teaching materials.